Changing the Direction of Suicide Prevention in the United States. Issue 4 (10th November 2016) - Reidenberg, Dan; Berman, Alan L.
Abstract : It is axiomatic that the goal of suicide prevention is the prevention of suicide. Yet in spite of significant efforts to this end since the middle of the last century, and most notably in the last decade, the rate of suicide in the U.S. has not declined; rather, it has increased. To address this issue, Suicide Awareness Voices of Education (SAVE) brought together leading prevention specialists from other public health problems where successes have been achieved, representatives from countries where suicide rates have declined, and U.S. based suicide prevention researchers and program directors, to "think outside the box" and propose innovative, scalable approaches that might better drive success in achieving desired results from U.S. suicide prevention efforts. The recommendations should challenge our preconceptions and force us outside our own mental constraints to broaden our perspectives and suggest catalysts for real change in suicide prevention.